KASHUBIAN IMAGES OF NON-KASHUBIANS. ON SOME LITERARY PROBLEMS WITH THE POSTDEPENDENCY FACTOR - Kalinowski, Daniel (Porównania, 2018)
The article focuses on the fundamental trends in the descriptions of Kashubian literature which portrays non-Kashubians (Florian Ceynowa, Henryk Derdowski, Aleksander Majkowski, Jan Rompski). Basically it gives here designate the tendency of sympathy and antipathy. The first takes place mainly in relation to the Poles who are seen from the perspective of a common struggle against Germanization. However, this is not a consistent trend because already in the discourse of the founder of the Kashubian identity, Florian Ceynowa, criticism of the Polish model of social and national characteristics characterological can be noticed. The second and opposite trend of presenting the other and the foreign is manifested most strongly in the literature Kashubian when including the German national element. It was almost always portrayed as evil and violent. There are, however, exceptions and sometimes the Germans are portrayed with respect and admiration. When it comes to the Jewish, the Kashubian literaturę does not take a consistent stand because of the small size of this social group in Pomerania. The foreigners / the others presented in the Kashubian literature are a threat in terms of numbers, civilization or culture for the Kashubians. Hence, Kashubian writers in their creations continuously juxtapose the domestic paradise with the external cultural factors. The newcomers from outside of Kashubia bring with them greed, immorality and a lack of ideological orientation, whereas they rarely inspire positive attributes. Thus, they become colonizers of the Kashubians and hold the state and sometimes even religious power.